Greek magic on the Atlantic? Homeric potions and mystic cults beyond the Pillars of Herakles. New comparanda and new interpretations - Pappa, Eleftheria (Romanitas - Revista de Estudos Grecolatinos, 2020)
The article reviews the evidence for cultic activity at the Orientalizing settlement of Alcácer do Sal (Portugal). It offers new comparanda for the assemblage of cultic artefacts identified at two locations and then interprets it in the broader context of Mediterranean interconnections. It is suggested that a cult brought by Phocaean Greek merchants, perhaps from southern Iberia where such cults are archaeologically attested during the same period, may explain the evidence better than the hypotheses so far formulated.